Kajian Aspek Tematik pada Novel "Saman" Karya Ayu Utami dan Novel "Nayla" Karya Djenar Maesa Ayu - Umiatun Sa'diyah (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
This researchaimed atobtainingan overall description of the mesandlevels in the novel Saman by AyuUtami and Nayla by Djenar Maesa Ayu. The method used was descriptive qualitative method. Theresults of this research showed that these two novels not only addressed the sexual exploitation, butalso addressed other issues which were more complex. Quantitatively, the occurrences of events, categorization of main theme levels within these two novels were among the theme of social levels.